Some aspects of the criminal policy of the Republic of Kazakhstan in the field of information security (Journal of actual problems of jurisprudence, 2018)
This article raises some urgent questions of criminal policy in the sphere of information security. The authors studied the existing jurisprudence in determining the position of criminal policy.Key words: information, information security, criminal policy.